Label-Free Rapid Detection of Pathogens with Antimicrobial Peptide Assisted Impedance Spectrometry. Issue 1793 (2015) - Jiang, Keren; Etayash, Hashem; Azmi, Sarfuddin; Thakur, Garima; Naicker, Selvaraj; Kaur, Kamaljit; Thundat, Thomas
ABSTRACT: An urgent need exist for developing handheld devices for rapid, sensitive, and specific detection method for pathogens. Here we demonstrate a rapid detection method for Gram-positive and Gram-negative bacteria using an impedance sensor array functionalized with antimicrobial peptides (AMPs). This impedance sensor screens pathogens in real-time and has comparable sensitivity with current detection methods like polymerase chain reaction (PCR) and immunoassay. Functionalized electrodes in array selectively bind to the corresponding bacteria strains, resulting in variations in the impedance modulus. Impedance variation is used to detect incubated bacterial cell concentration with a resolution of 1 cell µL -1 . The dynamic range of detection for both Gram-positive and Gram-negative bacteria is found to be 10 3 -10 6 cfu mL -1 . Micropatterned electrodes modified with AMPs in an impedimetric array offer an excellent platform for rapid and selective detection of pathogens in contaminated water and food products.